1996
DOI: 10.1051/forest:19960226
|View full text |Cite
|
Sign up to set email alerts
|

The effects of elevated CO2 and water stress on whole plant CO2 exchange, carbon allocation and osmoregulation in oak seedlings

Abstract: Summary— Seedlings of Quercus robur L grown under present (350 μmol mol -1 ) or twice the present (700 μmol mol -1 ) atmospheric CO 2 concentrations, were either maintained well-watered or subjected to a drought constraint late in the growing season (25 August 1993

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
3
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
3
23
3
2
Order By: Relevance
“…This may indicate a facultative compensatory mechanism (with differences amongst the three species) involving trade-offs between drought and low temperatures protection (Roberts et al 1980 (Tognetti et al 2000b), the variable and rather weak response of osmotic potentials to elevated [CO 2 ] suggest that the supposed beneficial effects of elevated [CO 2 ] with respect to tissue water relations should be considered with caution. CO 2 enrichment has been found to induce low osmotic potentials in several woody and herbaceous species (Sionit et al 1981;Paez, Hellmers & Strain 1984;Conroy et al 1988;Sasek & Strain 1989;Morse et al 1993;Ferris & Taylor 1994;Vivin et al 1996), while in other species no responses or even opposite responses have been observed (Reekie & Bazzaz 1989;Conroy et al 1990;Tschaplinski et al 1993;1995;Polley et al 1996;Allen et al 1998). It is possible that species which demonstrate a relatively small degree of active osmotic adjustment or/and adjustments of minor importance in drought resistance, such as many Mediterranean shrubs (Hinckley et al 1980), may intrinsically be less responsive to elevated [CO 2 ] in terms of osmoregulation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This may indicate a facultative compensatory mechanism (with differences amongst the three species) involving trade-offs between drought and low temperatures protection (Roberts et al 1980 (Tognetti et al 2000b), the variable and rather weak response of osmotic potentials to elevated [CO 2 ] suggest that the supposed beneficial effects of elevated [CO 2 ] with respect to tissue water relations should be considered with caution. CO 2 enrichment has been found to induce low osmotic potentials in several woody and herbaceous species (Sionit et al 1981;Paez, Hellmers & Strain 1984;Conroy et al 1988;Sasek & Strain 1989;Morse et al 1993;Ferris & Taylor 1994;Vivin et al 1996), while in other species no responses or even opposite responses have been observed (Reekie & Bazzaz 1989;Conroy et al 1990;Tschaplinski et al 1993;1995;Polley et al 1996;Allen et al 1998). It is possible that species which demonstrate a relatively small degree of active osmotic adjustment or/and adjustments of minor importance in drought resistance, such as many Mediterranean shrubs (Hinckley et al 1980), may intrinsically be less responsive to elevated [CO 2 ] in terms of osmoregulation.…”
Section: Discussionmentioning
confidence: 91%
“…It appears that lowering osmotic potential prevents perturbation of cell metabolism and also facilitates recovery from stress (Morgan 1984). Evidence of osmotic adjustment, paralleled by maintenance of higher water content and turgor pressure, has been found in several drought-stressed woody species exposed to elevated [CO 2 ] (Morse et al 1993;Vivin et al 1996). However, other authors (Conroy et al 1990;Tschaplinski, Norby & Wullschleger 1993;Tschaplinski, Stewart & Norby 1995;Polley et al 1996) have found limited effects of elevated [CO 2 ] on tissue osmotic potentials and adjustment to drought in several forest tree and shrub species.…”
Section: Introductionmentioning
confidence: 82%
“…Climate change -specifically, increased temperature and altered water balance -could lead to changes in the productivity of trees and the composition of forests. While oak species generally are well adapted to growth on drought-prone sites (Abrams, 1990) (Vivin et al, 1996). Leaf-level responses Responses to CO 2 are also measured at the leaf level.…”
mentioning
confidence: 99%
“…In comparison, they accounted for 57 % in maize roots [16] and for only 20 % in tissue extracts of white apices of oak roots [25]. It seems that the fraction of π due to inorganic solutes is higher in leaves than in roots: 45 % in oak [25] and above 90 % in barley [8]. As in maize roots [16] [17,26] [7].…”
Section: Introductionmentioning
confidence: 99%